Disparities in Health Outcomes of Return Migrants in Mexico. (28th October 2014) - Wilson, Fernando A.; Stimpson, Jim P.; Pagán, José A.
Abstract : Objective . The epidemiological paradox posits that immigrants in USA experience better health outcomes than nonimmigrants with similar socioeconomic status. However, little is known about the development of health problems over the life course for immigrants who return to their country of origin. Methods . The Mexican Migration Project provides detailed information on immigration, health, and socioeconomic status for 671 unauthorized migrants, 101 legal migrants, and 3, 748 nonmigrants. Cox regression estimated the adjusted hazard of developing hypertension, diabetes/prediabetes, poor mental health, and heart and lung problems. Results . Legal immigrants to USA did not have a significantly higher risk of having a self-reported diagnosis of hypertension, diabetes, heart or lung problems, or poor mental health compared to nonmigrants. However, the hazard ratio for unauthorized deported immigrants ranged from 2.25 (CI: 1.29–3.93) for diabetes to 4.43 (CI: 2.33–8.40) for poor mental health compared to nonmigrants. Conclusions . Health problems occur several years earlier among unauthorized immigrants compared to individuals who never migrated. Poor access to healthcare services combined with USA lifestyle and working conditions after migration to the USA may contribute to an increased risk for the development of chronic health conditions later in life.